EXPANDING THE SCOPE OF SCHOOL NURSING FOR COMPREHENSIVE CHILD AND ADOLESCENT HEALTH - Laila Ghalib Yehya Oraybi, Nabilah Ahmad Mohammed Asheri, Salha Ghaleb Oribi, Fatimah Omar Shame Al Semiry, Amal Mohammed Yahya Tumayhi, Munirah Aedh Al Huzari, Hamzah Abdulrahman Alkhalifah, Afaf Mohammed Hendi Hendi, ,; Raghad Ali Alshammari, Fawaz Abdullah Al Osaimy, Reem Ageel Bashakur, Sahar Mardha Aldawsari, Hajar Mudaysh Ali Alsalhabi, (Chelonian Research Foundation, 2022)
The possible involvement of nurses in health-promoting schools (HPS) initiatives is examined in this research. It makes the case that although though school nurses are present all over the world, their contribution to the advancement of HPS has been minimal. This paper looks at the causes of this and suggests ways to fix it, such as using action research and working with other medical experts. Key words: Public health, action research, school nursing, health promotion in schools, and partnership